2018
DOI: 10.1016/j.addma.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Material interactions in laser polishing powder bed additive manufactured Ti6Al4V components

Abstract: Laser polishing (LP) is an emerging technique with the potential to be used for post-build, or in-situ, precision smoothing of rough fatigue-initiation prone surfaces of additive manufactured (AM) components. LP uses a laser to re-melt a thin surface layer and smooths the surface by exploiting surface tension effects in the melt pool. However, rapid resolidification of the melted surface layer and the associated substrate thermal exposure can significantly modify the subsurface material. This study has used an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…This resulted in a coarse lamellae structure in the microstructure, as shown in Figure 2d. The dimension of the microstructure with an average size of 9.8 µm in the laser-polished layer is smaller than that of the substrate with an average size of 48.6 µm due to the rapid re-melting and solidification process [21].…”
Section: Microstructure Evolutionmentioning
confidence: 95%
“…This resulted in a coarse lamellae structure in the microstructure, as shown in Figure 2d. The dimension of the microstructure with an average size of 9.8 µm in the laser-polished layer is smaller than that of the substrate with an average size of 48.6 µm due to the rapid re-melting and solidification process [21].…”
Section: Microstructure Evolutionmentioning
confidence: 95%
“…1. 42 There are currently two forms of laser polishing. One is to fix the printed parts on a numerically controlled X-Y-Z stage and then perform polishing.…”
Section: Laser Polishing Mechanismmentioning
confidence: 99%
“…In addition to the selection of process parameters, the influence of other factors on the surface roughness of laser-polished Ti6Al4V alloy should also be taken into account. Tian et al 42 measured the surface roughness of laser-polished Ti6Al4V using a Nanofocus μScan laser profilometer and a white light interferometer with different resolutions and found that the Sa parameter was reduced from as-received 21.46 to 5.5 μm and 0.51 μm, respectively. The difference in the measurement results was mainly due to the size of the sampling area, namely, 2 mm × 3 mm and 0.13 mm × 0.17 mm.…”
Section: Surface Morphology and Roughnessmentioning
confidence: 99%
“…By varying the level of preheat the bed temperature is controlled by the software. For Ti-6Al-4V the intention is to maintain the bed at 650 °C, which is high enough to reduce the residual stresses in built parts to near zero 15 . This removes the need for a stress relief heat treatment following manufacture, typically required for selective laser melted (SLM) parts.…”
Section: Introductionmentioning
confidence: 99%